2023
DOI: 10.1001/jamanetworkopen.2022.54909
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Rhinoviruses and/or Enteroviruses in Pediatric Patients With Acute Respiratory Illness Before and During the COVID-19 Pandemic in the US

Abstract: ImportanceRhinoviruses and/or enteroviruses, which continued to circulate during the COVID-19 pandemic, are commonly detected in pediatric patients with acute respiratory illness (ARI). Yet detailed characterization of rhinovirus and/or enterovirus detection over time is limited, especially by age group and health care setting.ObjectiveTo quantify and characterize rhinovirus and/or enterovirus detection before and during the COVID-19 pandemic among children and adolescents seeking medical care for ARI at emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
(103 reference statements)
2
24
0
Order By: Relevance
“…As previously observed, HRV/ENT positivity on RM-PCR testing was common, with nearly half of all positive RM-PCR samples processed at our lab between 2016 and 2019 being positive for this pathogen. 3,4 Similar to previously published studies, we note that the mean number of days of symptoms before nasopharyngeal testing was approximately 5 days, and patients had on average nearly 2 outpatient visits related to viral symptoms following testing. These findings underscore the interruption to daily life that positivity with such a pathogen may confer, including missed days of childcare for children and work for their caregivers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As previously observed, HRV/ENT positivity on RM-PCR testing was common, with nearly half of all positive RM-PCR samples processed at our lab between 2016 and 2019 being positive for this pathogen. 3,4 Similar to previously published studies, we note that the mean number of days of symptoms before nasopharyngeal testing was approximately 5 days, and patients had on average nearly 2 outpatient visits related to viral symptoms following testing. These findings underscore the interruption to daily life that positivity with such a pathogen may confer, including missed days of childcare for children and work for their caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the known seasonality of FLU versus the year-round activity of HRV/ENT may prompt caregivers to present more rapidly for evaluation and influence a clinician's desire to test a patient with typical symptoms during the FLU season. 3,25 Additionally, we observed that children with FLU had fewer outpatient follow-up visits after testing compared to those with HRV/ENT. This could be related to the use of antiviral agents which shorten the course and severity of this infection.…”
Section: Hrv/ent Compared To Flumentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, 29 of the 70 non-PARDS cases (41.4%) had at least one underlying chronic illness. In a study by Rankin et al, 13 evaluating HRV and/or EV (+) cases before and during the COVID-19 pandemic, at least one chronic illness was present in 56.1% and 57.4% of cases in both periods.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of greater relative mitigation of respiratory hospitalizations in non-CMC compared with CMC in FY 2020 was surprising as we expected greater declines among CMC due to their elevated risk. Potential explanations for this observation include the ongoing circulation of other respiratory viruses during the pandemic for which CMC are at particular risk for hospitalization (eg, enterovirus), 34 unavoidable respiratory admissions unrelated to an infection (eg, noninfectious triggers for asthma or aspiration), and the use of nonpharmacologic infection-prevention strategies to reduce infection risk prepandemic among families of CMC. These explanations may also be relevant in understanding why older children who have a baseline lower risk of respiratory hospitalizations 35 were also observed to have greater relative decreases in respiratory admissions during the pandemic.…”
Section: Discussionmentioning
confidence: 99%